(untitled) (Fiep Bulletin - online, 2013)
The problem of search that stimulates this research was the following question: urinary incontinence affects quality of life in the period od pregnancy? Looking for answer. Was found the general objective that verifies problems about the urinary incontinence at quality of life pregnant. Was realized to field exploratory research with quantity character. To value this work it was used a quality of life questionnaire, king healt questionnaire. As the result from the search it was found some positive aspects about the examination relating momentaneous health of pregnant. Besides that, most of the pregnant say urinary incontinence doesn’t affect their social lives, neighter their physical activities and sexual relationship. So many pregnant that lose urine, then, don’t think changed the quality of life that each one has.